Sketching : the basics - Eissen, Koos (BIS Publishers, 2011)
The sequel, or more accurately, prequel, to the bestseller 'Sketching'. It explains the rudiments of learning to draw both clearly and comprehensively using step-by-step illustrations, examples and strategies